WHEAT QUALITY INDICES IN RELATION TO NITROGEN FERTILIZATION - Cosmin GHERBAN; Florin SALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study analyzed the variation of quality indices of wheat grains in relation to nitrogen fertilization. The experiment was carried out at the University of Life Sciences "King Mihai I" from Timisoara, Didactic and Experimental Resort (DER), in the 2021-2022 agricultural years. The wheat 'Venezio’ cultivar was cultivated in a non-irrigated system. Fertilization was done with ammonium nitrate in eight doses: 0, 40, 80, 120, 160, 200, 240 and 280 kg ha-1 N a.s. (a.s. – active substance). The studied quality indices showed variable values, between 13.8-16.4±0.30% in the case of the protein content (Pro), 27-34±0.83% in the case of the gluten content (Glt), 57-73±1.91% in the case of the Zeleny Index (Zel Ind), 74.6-76.5±0.20 kg hl-1 in the case of hectolitre weight (HW), respectively 11.5-11.8±0.04% in the case of moisture (Mstr). The variation of the quality indices values in relation to N was described by polynomial equations of the 2nd degree, under variable conditions of statistical safety (p<0.001 in the case of Pro, Glt, Zel Ind; p=0.0428 in the case of HW; p=0.0729 in the case of Mstr). The variation of Zel Ind in relation to other quality indices (Pro and Glt) was quantified by quadratic regression analysis (R2=0.996, p<0.001). According to PCA, a distribution and association of the variants was obtained in relation to the level of the evaluated quality indices: variants T1 and T2 were placed independently, variants T3 and T8 were associated with humidity (Mstr); variants T4 and T7 were associated with Pro, Glt and Zel Ind indices, and variants T5 and T6 were associated with HW. PC1 explained 87.168% of variance and PC2 explained 8.0113% of variance.